Bringing Principles and Fairness to the Sentencing of Murder - Mitchell, B; Roberts, J (2013)
The authors take a closer look at the current sentencing laws for murder and argue the need to change them. Expanding on the proposals described in the recently published book, Exploring the Mandatory Life Sentence for Murder, the authors provide a more detailed explanation for the new framework. The proposals suggest a new method of sentencing, and discuss how primary and secondary mitigating and aggravating favors can play a role in forming the suggested scheme. This article suggests that this method would constitute a more principled approach compared to mandatory life sentencing, by achieving higher levels of proportionality, greater consistency and restraint in the use of custody. While these proposals focus on the sentencing regime in England and Wales, the authors argue their relevance for other countries that also impose a mandatory life sentence framework. © 2013 Springer Science+Business Media Dordrecht.